Association of Serum Thyrotropin with Anthropometric Markers of Obesity in the General Population - Tiller, Daniel; Ittermann, Till; Greiser, Karin H; Meisinger, Christa; Agger, Carsten; Hofman, Albert; Thuesen, Betina; Linneberg, Allan; Peeters, Robin; Franco, Oscar; Heier, Margit; Kluttig, Alexander; et al. (Thyroid (New York, N.Y.), 2016)
Except from associations study with body weight, there are few longitudinal data regarding the association between thyroid function and anthropometric measurements such as waist circumference, waist-to-hip ratio, or waist-to height ratio. This study aimed to investigate the association of thyrotropin (TSH) at baseline with changes in different anthropometric markers between baseline and follow-up in the general population. Data were used from four population-based longitudinal cohort studies and one population-based cross-sectional study. A total of 16,902 (8204 males) subjects aged 20-95 years from the general population were studied. Body mass index, waist circumference, waist-to-hip ratio, and waist-to-height ratio were measured. Multivariable median regression models were calculated adjusting for the following covariates: age, sex, baseline value of the respective anthropometric marker, smoking status, follow-up-time period, and study site. In cross-sectional analyses, serum TSH within the reference range was positively associated with waist circumference (β = 0.94 cm [confidence interval (CI) 0.56-1.32]) and waist-to-height-ratio (β = 0.029 [CI 0.017-0.042]). These associations were also present for the full range of TSH. In the longitudinal analyses, serum TSH at baseline was inversely associated with a five-year change of all considered anthropometric measures within the prior defined study-specific reference range, as well as in the full range of serum TSH. High TSH serum levels were positively associated with current anthropometric markers, even in the study-specific reference ranges. In contrast, high TSH serum levels were associated with decreased anthropometric markers over a time span of approximately five years. Further research is needed to determine possible clinical implications as well as public health consequences of these findings.